Positioning Media Baru Dalam Menekan Pembiayaan Politik Elektoral Melalui Pendekatan Psikologi Politik - Halimur Rosyid (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
The aim of this article is to explore how media positioning is able to shift patterns of voting behavior so that it ultimately impacts the rationality of electoral political financing. The political psychology approach is present to provide an overview of how changes in political behavior will significantly change the framework of political financing design. This research uses a qualitative approach with descriptive methods. Literature studies are used to explore various data variants to be reduced and analyzed according to the relevance of the problem formulation that has been determined. Researchers collect secondary data from journals, media, news reports, books, magazines, or other statistical data that supports research. The results show that the high financing of electoral politics is caused by the weak positioning of new media as participatory control of politics. This weak control results in a tendency to stagnate changes in voting behavior if political news messages are in the interaction zone of abstain society and parochial culture society. At least positioning functions as a shaper of the public's political preferences so that when making every political decision they don't feel fooled or cheated.